Acute idiosyncratic liver injury after Cladribine treatment for multiple sclerosis: first case report and review on associated hepatic disorders. (November 2022) - Saraceno, Lorenzo; Pirro, Fiammetta; Stigliano, Rosa; Agostoni, Elio Clemente; Protti, Alessandra
In recent years, several disease-modifying therapies have been developed for the treatment of multiple sclerosis (MS). Cladribine transiently depletes B and T lymphocytes, with subsequent gradual cell recovery. No cases are reported in literature describing Cladribine drug-induced liver injury (DILI). We describe the case of a 19-year-old woman who developed acute idiosyncratic liver injury 12 days after treatment with Cladribine. Post-marketing adverse event reporting is of paramount importance to allow an early recognition and treatment. Moreover, evaluation of the physiopathological mechanism underlying drug-induced hepatic toxicity can provide clinicians with valuable instruments for prevention and treatment.